Державне регулювання енергетичної безпеки в національній економіці - Koval, Viktor (Dr. Viktor Koval, 2018)
Introduction. In the conditions of dependence on the imported energy resources there is a problem of ensuring stability of the energy industry with counteraction to changes of the ambient and a possibility of reacting to actions for providing competitive positions and advantages of the state. A number of problems in energy industry need a support of necessary level of the energy security on the basis of providing own extraction with volume reduction of imported energy resources, increasing of the national products’ competitiveness in the world markets, development of innovations and investments into energy efficient technologies. In such conditions, it’s important to apply actions for ensuring economic security of the energy sector through the creating of an efficient program for the protection of the national interests in the energy sector, which will contribute to the national economy development. Aim and tasks. The purpose of article is a researching of energy security and developing actions for state regulation of energy security. Research results. The article outlines the priority directions of the state policy on ensuring the energy sector development which are identified as a main risks and adverse factors of influence on functioning of energy industry of Ukraine. And the necessity of energy security systems formation at the state level is grounded. The perspective increasing directions of energy security are the establishment of more adapted to transformations system of state regulation with market self-regulation elements. The state regulation of energy security in conditions of high level internationalization of national economy should be aimed at the harmonization of its technological and institutional aspects which influence the development and implementation of energy technologies and projects related to renewable energy sources. The state regulation requires further active development of institutional conditions for use of alternative energy resources and energy saving based on renewable energy. Conclusion. To provide energy security it is necessary to improve the complex program of its development which will involve wide use of state regulation methods as well as public-private partnership development so the support of the implementation of investment projects will be provided. The important aspect in development of energy engineering is ensuring its economic security which will allow to level possible threats of the industry and to provide requirements of fuel and energy complex and industry for a long term. Energy security should be directed towards increasing energy efficiency which will promote reducing imports and depending on the supply of energy resources by other countries. State regulation of energy security should ensure the rational use of the energy sector potential and stable functioning of the energetic supply system which includes: implementation of energy efficiency and energy saving policies; increase of investment in energy engineering; reduction of environmental impact and emissions.